Lukács und Brecht - Pike, David,Brüggemann, Lore (Niemeyer, 1986)
Literaturverz. S. 265 - 271
Literaturverz. S. 265 - 271
Keywords: Lukács; Georg; Politische Theorie; Brecht; Bertolt; Sowjetunion; Literaturtheorie